Using Pythagorean Expectation to Determine Luck in the KFC Big Bash League. Issue 3 (14th June 2016) - Vine, Anthony J.
Abstract : Luck is an important factor in determining who wins sporting events. Despite this, the impact luck has in T20 cricket has yet to be quantified. The aim of this study is to adapt the Pythagorean Expectation formula to apply to T20 cricket using results from the Big Bash League. This adapted formula is then used to determine how "lucky" each team has been by comparing the expected with actual win totals. It is found that runs scored and runs allowed are from independent translated Weibull distributions, suggesting the formula is valid in T20 cricket. An exponent of 7.41 is determined as most appropriate.